2021
DOI: 10.32604/csse.2021.014301
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Education with Vision 2030 Using Augmented Reality

Abstract: Vision 2030 requires a new generation of people with a wide variety of abilities, talents, and skills. The adoption of augmented reality (AR) and virtual reality is one possible way to align education with Vision 2030. Immersive technologies like AR are rapidly becoming powerful and versatile enough to be adopted in education to achieve this goal. Technologies such as AR could be beneficial tools to enhance maintainable growth in education. We reviewed the most recent studies in augmented reality to check its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This system includes three scenarios: system start scenario, system setup scenario, and exhibition hall scenario [26] . The system first enters the system start scenario and then clicks the button to enter the other two scenarios [27] . Each interface element, such as the background and button, is imported into Unity as an independent image.…”
Section: Interactive Module Developmentmentioning
confidence: 99%
“…This system includes three scenarios: system start scenario, system setup scenario, and exhibition hall scenario [26] . The system first enters the system start scenario and then clicks the button to enter the other two scenarios [27] . Each interface element, such as the background and button, is imported into Unity as an independent image.…”
Section: Interactive Module Developmentmentioning
confidence: 99%
“…Wazirali [48] examined current augmented reality research to determine whether it was appropriate and compatible with Vision 2030's educational objectives. A total of sixty articles published between 2000 and 2020 were considered for review.…”
Section: Exploration Of the Existing Literature Reviewsmentioning
confidence: 99%
“…For example, it was observed that using the AR application makes it easier for students to comprehend the subjects which they had difficulties comprehending with the conventional methods [ 19 ]. Moreover, it was found that AR technology provides the skill and experience which come with practice [ 20 23 ]. The AR technology does not only transfer knowledge but also helps users to actively make practice [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two approaches in the field of education stand out in the use of AR technology. The first approach is task-focused applications that are designed for transferring know-how and skills to specific individuals [ 21 23 ]. The second is general applications that aim to entertain while presenting the most basic information.…”
Section: Literature Reviewmentioning
confidence: 99%